Urgensi Pembentukan Undang-Undang Fintech Di Indonesia: Harapan Dan Realita Di Era Pandemic Covid-19 - Didik Irawansah; Wardah Yuspin; Ridwan Ridwan; Nasrullah Nasrullah (SASI, 2021)
The growth of Fintech in Indonesia is very rapid, this condition is directly proportional to the legal problems that arise, the legal policy of regulation and protection of Fintech is still focused on the OJK, while the OJK still has many weaknesses in the implementation of supervision and protection of fintech activities, especially in the era of the covid pandemic. -19. The purpose of this study, first, by outlining the legal regulations issued by Bank Indonesia and the Financial Services Authority regarding fintech in Indonesia by looking at the legal weaknesses so that it is important to establish the Fintech Law. second, the urgency of the establishment of a fintech law on fintech consumer protection in Indonesia. Meanwhile, the importance of this research is that it will explain the development of the fintech industry in Indonesia, especially during the Pandemic, where the fintech industry experienced significant development so that this is an idea to provide a clear legal framework for the fintech industry. The research method used is normative juridical using library data and observations of fintech developments through library studies. Research findings show that so far fintech in Indonesia has used regulations contained in the POJK and PBI as the basis for implementing fintech, although it is felt that the regulations issued by POJK and PBI have not been able to provide maximum legal protection for the implementation of the fintech industry. so it is necessary to establish a law in order to provide legal protection for the development of the fintech industry now and in the future.